THE EFFECT OUTDOOR STUDY TO THE STUDENTS ACTIVENESS IN SENIOR HIGH SCHOOL - Andri Estining Sejati; Nasarudin N; Fahrudi Ahwan Ikhsan (Geographica: Science and Education Journal, 2019)
Problems in the class indicate students are less active in learning. Students are more dominant in receiving one-way material. The low desire of students in learning participation in the form of asking, answering, or presenting. The outdoor study is the chosen learning method to overcome these problems. The outdoor study is useful for student knowledge, learning, and student motivation. This study aims to determine the effect of outdoor study on the activeness of high school geography students. This research is included in a quantitative methodology with a type of quasi experiment. The researcher determined purposely XI IIS 1 as the experimental class and XI IIS 2 as the control class. Research in Muhammadiyah 1 Babat High School, Lamongan Regency even semester 2015/2016 academic year. The data in this research were analyzed using descriptive quantitative with percentage. The results show that the application of outdoor study provides a change in student active; this can be seen from the category of the active per student in the experimental class, none of them get less active. The average overall active there is a difference of 12.43 from the control class. The average score of questions asked to answer, respond, and presentations of the experimental class are all higher than the control class